PENGARUH KEPEMIMPINAN MANAJERIAL TERHADAP PENGEMBANGAN KARIER DAN KINERJA GURU SMP NEGERI SE KABUPATEN SUKOHARJO - nur sukri (Jurnal Pendidikan Nusantara, 2021)
This research was conducted on Sukoharjo district which covered 120 teachers of junior high school as respon dent sampling selection method using purposive random sampling collection data with send the survey using questionnaire to respondent this research by utilizing structural equation modeling (SEM) to analyze data. The result of this research show the indiviudla characteristics has significant effect on career development and performance, career development and managerial leadhership has significant effect on organizational commitment, and organizational commitment, and organizational commitment has significant effect on teacher performance